IMPLEMENTASI MODEL PROBLEM BASED LEARNING BERBANTU MEDIA POWTOON DALAM MENINGKATKAN MINAT BELAJAR PPKN SISWA SEKOLAH DASAR - Diah Retno Wati; Sutrisna Wibawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effectiveness of the implementation of the Problem Based Learning (PBL) model assisted by Powtoon media in increasing elementary school students' interest in learning Civics. This research uses quantitative methods with a quasi-experimental pretest-posttest group design. The research subjects were 30 grade VI students of SDN Tegowanuh who were divided into two groups, namely the experimental group and the control group. The experimental group was treated with PBL learning assisted by Powtoon media, while the control group was treated with conventional learning. Research data were collected through Civics learning interest tests and observations of student learning activities. The results showed that there was a significant difference between the interest in learning Civics of experimental and control group students. It can be seen from the results of the average value of the control group 73.6 while in the experimental group the average value is 85.2. This shows that the implementation of the Problem Based Learning (PBL) model assisted by Powtoon media is effective in increasing elementary school students' interest in learning Civics.